Scelerotherapy with 5% Phenol in Almond Oil in Treatment of Rectal Prolapse in Children: Experience of District Head Quarter Hospital Kohat - WASEEM MUHAMMAD, FAZAL AHMED (Journal of Fatima Jinnah Medical University, 2018)
Background: Rectal prolapse is an uncommon condition.Increased abdominal pressure is the main causative factor. Failure of conservative measures should be followed by surgical corrective procedures like Sclerotherapy followed by more aggressive surgery, including abdominal posterior rectopexy , abdominal or perineal bowel resection, transanal suture rectosacropexy , and posterior sagittal Anorectoplasty procedures have been described. Our study was conducted to observe the results of Sclerotherapy in young children. Objective: To assess the efficacy ofscelerotherapy in treating children with rectal prolapse . Material And Methods: 200 patients were included in our study. The study was conducted in the Surgical Department of District Hospital Kohat. Study design was Observational . All the patients below 5 years of age and having first degree rectal prolapse were included in our reseach. Patients having associated rectal bleeding and those having infective causes for diarrhea were excluded from the study. Regular follow up was done for 6 years. Scelerosant used was 5% Phenol in Almond Oil. The procedures were done by consultant surgeon to minimize procedural Bias. Results were analyzed using SPSS 17. Results: 200 patients were studied. All patients were below 5 yrs of Age. All the patients were injected with 5 % Phenol in Almond oil. Patients were followed up for 2 years.6 weekly for first 6 months then 3 monthly for two years. It was observed that 15 patients lost Followup. 168 (84%) patients were cured by using scelerotherapy. 5 patients developed Complication (2 excoriation of rectal Mucosa, 1 proatatitis/cystitis and 2 bleeding) and 7 recurrence Conclusion: Injection sclerotherapy is simple and should be considered as the first line treatment of rectal prolapse after failure of conservative measures.